Associations of Adolescent Weight Status and Meeting National Obesity‐Related Recommendations. (2nd November 2017) - Cook, Jessica A.; McCormick, Emily V.; Mickiewicz, Theresa E.; Davidson, Arthur J.; Main, Deborah S.
ABSTRACT: BACKGROUND: Adolescent overweight and obesity are serious health risks, with prevalence varying by sociodemographic group. Studies link children's weight status and sex/race–ethnic differences with meeting recommendations for physical activity and diet. But, research examining the intersection of sociodemographic characteristics, behavior, and weight status is limited. This paper aims to identify sociodemographic differences in the association between adolescent weight status and meeting 6 national obesity‐related recommendations. METHODS: In 2011–2012, the Healthy Kids Colorado Survey was administered to all Denver high school students. Using descriptive and multivariate modeling, we examined subgroup associations between students' self‐reported weight status and physical activity and diet. RESULTS: Students (N = 6652) who met at least 1 recommendation were less likely to be at an unhealthy weight (OR = 0.87); also true for students who met at least 1 physical activity recommendation (OR = 0.80). However, the association varied across subgroups. The association between weight status and meeting at least 1 nutritional recommendation (OR = 0.91) was inconsistent across subgroups. Unexpected patterns also emerged in subgroup associations between meeting specific recommendations and weight status. CONCLUSIONS: Identifying subgroup differences in meeting recommendations and the association with weight status is important in identifying high risk groups and improving policy and programs that target childhood obesity prevention.